We know that:

If `y(s)= b/(s^2 + b^2), `

`==gt y(t) = sin(bt)`

We are given that:

`y(s) = 3/(s^2+ 4)`

We will rewrite as:

`y(s)= 2/(s^2 + 2^2) * 3/2 `

`==gt y(s)= (3/2) 2/(s^2 + 2^2)`

**==> y(t)= 3/2 * sin(2t)**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now